THE EFFECT OF PROFITABILITY, COMPANY SIZE AND EARNINGS QUALITY ON COMPANY VALUE WITH LEVERAGE AS A MODERATING VARIABLE: A CASE STUDY IN THE TECHNOLOGY INDUSTRY IN SOUTHEAST ASIA - Maria Yuliasti Kalan; Robiur Rahmat Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine the effect of Profitability, Company Size, and Earnings Quality on Firm Value with Leverage as a moderating variable in technology sector companies in Southeast Asia. This study uses panel data covering 123 observations from 41 technology companies operating in Indonesia, Malaysia, and Singapore during the 2022–2024 period, with data processing carried out using Stata 17 software. Determination of the best analysis model is based on the Hausman Test which shows that the Random Effect Model (REM) is the most appropriate model with a probability value of 0.9073. The results of the analysis indicate that Profitability, Company Size, and Earnings Quality have a positive relationship with Firm Value, but this effect is not statistically significant. Furthermore, testing of moderating variables shows that Leverage does not play a role in moderating the relationship between Profitability, Company Size, or Earnings Quality on Firm Value. The coefficient of determination (R²) value of 0.0561 indicates that the combination of independent variables and moderating variables is only able to explain 5.61% of the variation in Company Value, while the remainder is influenced by other factors outside the research model. These findings indicate that investors in the technology sector in Southeast Asia rely not only on internal financial indicators to assess company value, but also consider external and non-financial factors. Therefore, companies need to improve transparency, the quality of information disclosure, and the implementation of good governance and sustainability to increase company value in the market.